FAKTOR – FAKTOR YANG BERHUBUNGAN DENGAN STIGMA IBU RUMAH TANGGA TERHADAP ODHA DI WILAYAH LOKALISASI TEGAL PANAS KABUPATEN SEMARANG - Puri Fatma Sari; Syamsulhuda Budi Musthofa; Zahroh Shaluhiyah (Jurnal Kesehatan Masyarakat (Undip), 2022)
One of the things that challenges HIV/AIDS redustion is stigma and 35 million people with HIV/AIDS (PLWHA). The number of HIV/AIDS cases in Semarang Regency has increased every year, where the District of Bergas the region with the highest case in Semarang Regensy in 2010-2018. The purpose of this study was to analyze the factors associated with the  stigma of housewives against PLHA in the Tegal Panas localization area, Semarang Regency. This study used a quantitative method with a cross sectional design. Respondents in this study were housewife in the Tegal Panas localization are, amounting 100 people. The result showed that there was still stigma among housewives in the Tegal Panas area brothel which supported the existence of stigma (40%).  The variables associated with the stigma of housewives towards PLWHA were education, knowledge, and neighbor support . The unrelated variables were age, perception, access ti information, family support, support from community leaders and support from health workers. There is still a stigma in the community in the Tegal Panas Localization area, it is faered that it can worsen the quality life of PLWHA.